Evaluating the causes of delays in the construction of Telecommunication Towers in Ghana - Daniel, Anaba (2021)
A thesis submitted to the Department of Construction Technology and Management, Kwame Nkrumah University of Science and Technology, Kumasi, in partial fulfillment of the requirements for the award degree of Master of Science in Project Management.